2010
DOI: 10.1002/pmic.200900445
|View full text |Cite
|
Sign up to set email alerts
|

Investigating protein isoforms via proteomics: A feasibility study

Abstract: Alternative splicing (AS) and processing of pre-messenger RNAs explains the discrepancy between the number of genes and proteome complexity in multicellular eukaryotic organisms. However, relatively few alternative protein isoforms have been experimentally identified, particularly at the protein level. In this study, we assess the ability of proteomics to inform on differently spliced protein isoforms in human and four other model eukaryotes. The number of Ensembl-annotated genes for which proteomic data exist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
59
1
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(64 citation statements)
references
References 61 publications
3
59
1
1
Order By: Relevance
“…Another important issue in the discovery of alternative splice forms at the protein level is the low number of splicespecific peptides actually identified, an issue that has been revealed by work reported in the literature (17,19,22,24,25,30,31). Part of the reason for the low number of alternative splice variants detected are the technical differences between RNA-Seq and bottom-up proteomics, namely sequence coverage and detection sensitivity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Another important issue in the discovery of alternative splice forms at the protein level is the low number of splicespecific peptides actually identified, an issue that has been revealed by work reported in the literature (17,19,22,24,25,30,31). Part of the reason for the low number of alternative splice variants detected are the technical differences between RNA-Seq and bottom-up proteomics, namely sequence coverage and detection sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Transcripts can be sensitively (Ͻ1 transcript/cell) and completely (100% sequence coverage) characterized, but for proteins, only moderately or highly expressed (Ͼ1 protein molecules/cell) proteins are usually detected and amino acid sequence coverage is typically low (ϳ5-25%). Alternatively spliced proteins are difficult to detect because 1) they have lower cellular abundances than the canonical forms, 2) require at least one splice form-specific peptide for unambiguous detection, likely one spanning a junction or residing in a splice form-specific exon (24), and, 3) the alternative splice variant sequence is sometimes not yet in the database.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, there are currently seventeen differently spliced transcript variants of human brain-derived neurotrophic factor (BDNF) in The National Center for Biotechnology Information (NCBI) RefSeq database (ftp://ftp.ncbi.nih.gov/refseq/H_sapiens/ mRNA_Prot/human.rna.fna.gz, May 25, 2010). The proteomic approaches for identifying the splicing variants at the protein level are still under development, although current research has been encouraging, as shown in a recent report by Blakeley [32]. Blakeley et al assessed the ability of proteomics to identify differently spliced protein isoforms in human and four other model eukaryotes and found support for over 600 alternatively spliced (AS) genes in chicken via proteomics.…”
Section: Cerebrospinal Fluid: Another Resource For Proteomic Studiesmentioning
confidence: 94%